Louis Vuitton’s Strategies for Enhancing Customers’ Engagement on Instagram and Weibo - Xincheng Wu (Media and Intercultural Communication: A Multidisciplinary Journal)
Social media platforms, especially Instagram and X (former Twitter), play an indispensable role in disseminating information all over the world. This research article aims to figure out the strategies adopted by Louis Vuitton on Instagram and Weibo to improve its brand publicity and brand awareness among its customers. Content analysis is utilized to give a comprehensive picture and objective implications. The contents posted from 1-30 May 2023, are chosen to gather first-hand information. Four types of publics and three social-mediated publics are illustrated to facilitate the reader's understanding of social network analysis. Furthermore, the findings revealed different approaches adopted by Instagram and Weibo to cater to local traditions and cultures to make more profits and occupy a larger market share. Collectivism and individualism are favored by Weibo and Instagram, respectively, which is in line with Eastern and Western preferences.